ANALISIS KEARIFAN LOKAL TANAMAN KARET RAMAH LINGKUNGAN DI KECAMATAN GAROGA KABUPATEN TAPANULI UTARA - Erna hutabarat; Eri Sayamar; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research carried out at  medium region of Garoga regency of Tapanuli utara  with the selected villages as a place of research are village Garoga Sibargot and village Padang Siandomang. The aims of this study are to identify local knowledge ever in rubber production businesses, analyzing the practice of local knowledge on rubber production businesses in garoga district, knowing the local knowledge environmentally is friendly in cultivation the rubber plant. Benefits on this study are collecting and reminded back about old culture has gone, and still exists so that can be used as a reference to the future. The sampling technique in this research used technique snowball sampling or carried out with the chain by asking information on those who have interviewed or contacted earlier, and forward. And techniques of data collection be used in this research are in-depth interviews with key informants and the questionnaire .Data analysis is use the 5W 1H method, analysis of likert and analysis of SWOT. Local knowledge is a form of knowledge, belief, rules, customs, and habit has done by a society that who honor the  norms and the cultural values has been existed and lowered from ancestor to children and children for running daily life. In this research there are local knowledge in the cultivation of  Rubber plants , where 80 percent of the people is rubber farmers. This thing proved that they still run the local wisdom that hereditary there with them, although procedures, a customary ceremony and also rules are already gone. The local wisdom of  the rubber plant totaled 71 the local wisdom , ever and performed farmers ancients totaled 34 and now  the performed farmers totaled are 4. The local wisdom has ever seen and done farmers ago, and still used by farmers now 33 totaled namely the local wisdom. Key Word: local wisdom, rubber, and environment